Parasitic helminths of wild vertebrates from San Juan province, Argentina - Castillo, Gabriel Natalio (Acta Scientiarum. Biological Sciences, 2025)
We present a list of parasitic helminths found in wild vertebrates from San Juan Province, Argentina. The list encompasses various helminth species parasitizing fish, amphibians, reptiles, birds, and mammals. The data were sourced from national and international journals up to December 2023. A systematic bibliographic search was conducted across electronic databases such as SciELO (Scientific Electronic Library Online), Dialnet, and Google Scholar, as well as institutional repositories. Congress abstracts were excluded from consideration. The compiled list documents 35 helminth taxa associated with 39 species of wild vertebrates, spanning different taxa of fish, amphibians, reptiles, mammals, and birds. The 35 helminth taxa are distributed across 21 genera, 16 families, 6 orders, and 2 phyla, parasitizing a total of 39 vertebrate hosts: 2 fish species, 6 amphibians, 21 reptiles, 8 mammals, and 2 bird species. Nematodes exhibited the highest number of taxa, while cestodes were the least recorded or studied. Among vertebrates, reptiles represent the most extensively studied group, with the genus Liolaemus being the most analyzed, followed by the genus Phymaturus. Birds and fish, however, remain the least studied. This taxonomic list of helminths in association with vertebrate hosts is fundamental for understanding ecosystem dynamics. Notably, this represents the first taxonomic list of parasitic helminths in vertebrates from San Juan Province, Argentina, contributing to a deeper understanding of current parasite-host interactions.